RANCANG BANGUN SISTEM PEMINJAMAN BARANG DAN RUANGAN DI UNIVERSITAS BANTEN JAYA BERBASIS WEBSITE - Widyawati Widyawati; Aisyah Fatamawati; Tifani Intan Solihati; Persis Haryo Winasis (LPPM Unbaja, 2025)
The Facilities and Infrastructure Unit at Banten Jaya University (UNBAJA) plays a crucial role in supporting the institution’s operational and academic excellence. As the university grows, the need for efficient, accurate, and technology-driven systems becomes increasingly important, particularly in managing resources such as rooms, goods, and vehicles. Currently, the loan system for these assets is still conducted manually, relying on inventory logbooks and Microsoft Office tools. This conventional method often results in data redundancy, errors in data entry, and frequent conflicts in scheduling due to lack of real-time updates and validation mechanisms. To address these challenges, this research focuses on developing a web-based loan system designed to streamline and digitize the borrowing process for students, lecturers, and administrative staff. The system is built using the Agile development methodology, ensuring iterative feedback and continuous improvement. It utilizes PHP as the core programming language, with Laravel serving as the framework and MySQL as the database engine. The application design is modeled using Unified Modeling Language (UML) to provide clear and structured system architecture. Functionality and reliability are tested through the Black Box testing method, ensuring all system functions perform as expected. The implementation of this system significantly improves the efficiency of the loan process, enhances data accuracy, and facilitates better inventory and usage reporting. Additionally, the system enforces a First In, First Out (FIFO)mechanism, promoting fairness and orderliness in resource distribution. This digital transformation marks a strategic step in aligning UNBAJA’s operations with modern information technology practices.